The Positioning Accuracy Based on the UWB Technology for an Object on Circular Trajectory - Damian Grzechca; Krzysztof Hanzel (International Journal of Electronics and Telecommunications, 2018)
This paper presents the comparison of filtering methods – median filtration, moving average Kalman filtration and filtration based on a distance difference to determine the most accurate arm length for circular motion, as a model of wind turbine propellers movement. The experiments have been performed with the UWB technology system containing four anchors and a tag attached to 90cm arm that was rotated with speed up to 15.5 rad/s (as a linear speed of 50km/h). The trilateration concept based on the signal latency has been described in order to determinate the position of an object on circular trajectory. The main objective is the circle plane rotation (parallel and perpendicular) with respect to the anchors plane reference system. All research tasks have been performed for various cases of motion schemes in order to get the filtration method for object in motion under best accuracy goal. Filtration methods have been applied on one of two stages of the positioning algorithm: (1) on raw data got from the single anchor-tag (before trilateration); (2) on the position obtained from four anchors and tag (after trilateration). It has been proven that the appropriate filtering allows for higher location accuracy. Moreover, location capabilities with the use of UWB technology – shows prospective use of positioning of objects without access to other positioning forms (ex. GPS) in many aspects of life such as currently developing renewable, green energy sources like wind turbines where the circular motion plays an important role, and precise positioning of propellers is a key element in monitoring the work of the whole wind turbine.